Responsiveness of Volatility Analysis of the Jakarta Islamic Index on Macroeconomic Variables - Eni Susanti; Ratno Agriyanto; Musahadi Musahadi; Saifudin Zuhri (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2021)
This study aims to analyze the inﬂuence and response of the Jakarta Islamic Index (JII) volatility to changes in macroeconomic variables. VECM was used to examine the long-and short-term eﬀects, while IRF was used to analyze the JII response. Data were obtained from BPS, BI, and Yahoo Finance monthly from 2015-2020 using global macroeconomic ﬁscal variables, including inﬂation, BI and Exchange Rates, Industrial Production Index, World Oil Price, Malaysia Hijrah Shariah Index, and DJIM Malaysia Titan 25 Index. The results show that JII is inﬂuenced by inﬂation variables, BI rate, IPI, OP, MHS, and DJIM in the long term but not the exchange rate. Furthermore, it is inﬂuenced by BI rate, IPI, OP, MHS, and DJIM in the short term, while the exchange rate and inﬂation have no signiﬁcant eﬀect. Macroeconomic variable shock inﬂuence JII by 52,27% while the rest is inﬂuenced by other variables outside the model. This research implies that the JII index is very sensit ive to economic changes.